The Influence of Ezekiel in the Fourth Gospel, Intertextuality and Interpretation. - William G. Fowler; Michael Strickland (Biblical Interpretation Series, 2018)
This monograph presents important research regarding the Fourth Gospel's use of Scripture, specifically the book of Ezekiel. It provides the first detailed comparison of the theological vocabularies of the two works, identifying intertextual links and themes. This is a major update and expansion of the doctoral dissertation of William Fowler from 1995 (\'The Influence of Ezekiel in the Fourth Gospel\', PhD diss. Golden Gate Baptist Theological Seminary).